Polyethylene resin composition and polyethylene resin packaging material
By using ethylene-α-olefin copolymers with a specific melt flow index and carbon atom number, combining inorganic compounds and high-density polyethylene, the problem of poor performance of polyethylene-based resin packaging materials in the prior art after adding inorganic compounds is solved, and excellent forming properties, bag making processability and film strength are achieved.
Patent Information
- Application Number
- CN202080106882.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-09-16
AI Technical Summary
After the addition of inorganic compounds, the existing polyethylene-based resin packaging materials have poor formability, bag making processability and film strength.
An ethylene-α-olefin copolymer with a melt flow index of a specific range and a carbon atom of α-olefin is 6 to 8, and an inorganic compound and a high-density polyethylene are combined to form an excellent polyethylene-based resin composition.
Even when the inorganic compound is added, excellent forming properties, bag making processability and film strength can be maintained, thereby improving the overall performance of the packaging material.
Smart Images

Figure GDA0005247638860000101 
Figure GDA0005247638860000111
Abstract
Description
Technical Field
[0001] The present invention relates to a polyethylene resin composition and a polyethylene resin packaging material. Background Art
[0002] Polyethylene resin packaging materials are used for many purposes besides garbage bags, shopping bags, fashion bags, etc. In recent years, with global warming, there is a strong demand to reduce the amount of carbon dioxide produced, and it is very important to suppress the amount of resin used. As a method for reducing the amount of resin used, it is known to add inorganic compounds to the resin while ensuring formability. Patent documents 1 and 2 disclose adding calcium carbonate to the resin.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 3366942
[0006] Patent Document 2: Japanese Patent Application Publication No. 2018-21121 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, the films mixed with calcium carbonate described in Patent Documents 1 and 2 are inferior in bag-making processability by heat sealing and film strength.
[0009] An object of the present invention is to provide a polyethylene resin composition which has excellent moldability even when an inorganic compound is added and can produce a film having excellent bag-making processability and film strength, and a polyethylene resin packaging material using the polyethylene resin composition.
[0010] Solutions to Solve Problems
[0011] The present inventors have found that by using an ethylene-α-olefin copolymer having a melt flow index in a specific range and an α-olefin having 6 to 8 carbon atoms, excellent moldability and bag-making processability can be ensured even when an inorganic compound is blended, thereby obtaining a polyethylene resin packaging material having excellent film strength.
[0012] The present invention has the following aspects.
[0013] [1] A polyethylene resin composition, comprising an inorganic compound, an ethylene-α-olefin copolymer and a high-density polyethylene, wherein at least a portion of the ethylene-α-olefin copolymer is an ethylene-α-olefin copolymer A having 6 to 8 carbon atoms in the α-olefin and a melt flow index of 1.0 g / 10 min to 2.0 g / 10 min, the content of the inorganic compound is 50% to 80% by mass relative to the total mass of the resin composition, the content of the ethylene-α-olefin copolymer A is 10% to 25% by mass relative to the total mass of the resin composition, and the content of the high-density polyethylene is 5% to 15% by mass relative to the total mass of the resin composition.
[0014] [2] The polyethylene resin composition according to [1], wherein the melting point of the ethylene-α-olefin copolymer A is 90° C. or higher and 130° C. or lower.
[0015] [3] The polyethylene resin composition according to [1] or [2], wherein the inorganic compound is calcium carbonate.
[0016] [4] A polyethylene resin packaging material, comprising the polyethylene resin composition according to any one of [1] to [3].
[0017] [5] The polyethylene resin packaging material according to [4], which is a garbage bag, a shopping bag, a fashion bag, a storage bag or a packaging bag.
[0018] Effects of the Invention
[0019] According to the present invention, there can be provided a polyethylene resin composition having excellent moldability even when an inorganic compound is added and capable of obtaining a film having excellent bag-making processability and film strength, and a polyethylene resin packaging material using the polyethylene resin composition. DETAILED DESCRIPTION
[0020] [Polyethylene resin composition]
[0021] The polyethylene resin composition of the present invention (hereinafter referred to as "PE resin composition") contains an inorganic compound and an ethylene-α-olefin copolymer.
[0022] The ethylene-α-olefin copolymer is a copolymer obtained by copolymerizing ethylene and α-olefin, preferably a linear low-density polyethylene (LLDPE). At least a portion of the ethylene-α-olefin copolymer contained in the PE-based resin composition of the present invention is an ethylene-α-olefin copolymer A (hereinafter referred to as "copolymer A") having α-olefin carbon atoms of 6 to 8 and a melt flow index (MFR) of 0.8 g / 10 minutes or more and 4.0 g / 10 minutes or less.
[0023] The carbon number of the α-olefin used in the copolymer A is 6 to 8. Specific examples of the α-olefin used in the copolymer A include 1-hexene and 1-octene. The α-olefin used in the copolymer A may be one kind or two or more kinds.
[0024] The MFR of copolymer A is 0.8g / 10 minutes or more and 4.0g / 10 minutes or less, preferably 0.8g / 10 minutes or more and 2.0g / 10 minutes or less, more preferably 0.8g / 10 minutes or more and 1.5g / 10 minutes or less, and further preferably 0.8g / 10 minutes or more and 1.2g / 10 minutes or less. If the MFR of copolymer A is above the lower limit of the above range, excellent formability can be ensured even if the molding temperature is low, so the deterioration of copolymer A can be suppressed. If the MFR of copolymer A is below the upper limit of the above range, the melt tension will not become too low, so film forming becomes easy.
[0025] In addition, MFR is a value obtained by applying a load of 2.16 kg to a resin (polymer) heated to 190° C. and measuring the amount of resin flowing out from an orifice with a diameter of 2.09 mm for 10 minutes.
[0026] The melting point of copolymer A is preferably 90° C. to 130° C., more preferably 100° C. to 125° C. If the melting point of copolymer A is above the lower limit of the above range, the sealing shape during bag making by heat sealing becomes good. If the melting point of copolymer A is below the upper limit of the above range, the heat sealing time can be shortened and the bag making speed (production speed) is improved.
[0027] In addition, the melting point is the temperature corresponding to the melting peak measured by differential scanning calorimetry (DSC).
[0028] The copolymer A may be a copolymer having an MFR satisfying the above range among LLDPE containing 6 carbon atoms of an α-olefin (C6-LLDPE) and LLDPE containing 8 carbon atoms of an α-olefin (C8-LLDPE).
[0029] The copolymer A contained in the PE-based resin composition may be one kind or two or more kinds.
[0030] The method for producing the copolymer A is not particularly limited, and examples thereof include polymerization using a Ziegler-type catalyst based on a transition metal such as titanium, polymerization using a Phillips-type catalyst based on a chromium-based catalyst, and polymerization using a Kaminsky-type catalyst based on a metallocene-based catalyst. The polymerization method may be any of a solution polymerization method, a slurry polymerization method, a gas phase polymerization method, and a high-pressure ion polymerization method. In addition, the polymerization may be a single-step polymerization or a multi-step polymerization method of more than two steps.
[0031] The PE resin composition of the present invention may contain other ethylene-α-olefin copolymers other than copolymer A. The other ethylene-α-olefin copolymers are not particularly limited, and examples thereof include ethylene-α-olefin copolymers having 4 carbon atoms in the α-olefin, and preferably LLDPE (C4-LLDPE) having 4 carbon atoms in the α-olefin. The other ethylene-α-olefin copolymers other than copolymer A contained in the PE resin composition may be one or more.
[0032] In the range that does not impair the effects of the present invention, the PE-based resin composition of the present invention may also contain, in addition to copolymer A, high-density polyethylene (HDPE), low-density polyethylene (LDPE), ultra-low-density polyethylene (VLDPE), ethylene-vinyl acetate resin (EVA), ethylene-vinyl alcohol copolymer (EVOH), ethylene-propylene copolymer, etc.
[0033] The resin component contained in the PE-based resin composition of the present invention is preferably the copolymer A alone, a combination of the copolymer A and C4-LLDPE, a combination of the copolymer A and HDPE, or a combination of the copolymer A, C4-LLDPE, and HDPE.
[0034] Relative to the gross mass of the PE resin composition, the content of the copolymer A in the PE resin composition is 10% by mass or more and 50% by mass or less, preferably 13% by mass or more and 50% by mass or less, more preferably 16% by mass or more and 50% by mass or less. If the content of the copolymer A is above the lower limit of the above range, sufficient film strength can be obtained. If the content of the copolymer A is below the upper limit of the above range, the effect of suppressing the amount of resin can be fully obtained.
[0035] When the PE resin composition of the present invention contains C4-LLDPE, the content of C4-LLDPE in the PE resin composition is preferably 10% by mass or more and 40% by mass or less, and more preferably 20% by mass or more and 40% by mass or less, relative to the total mass of the PE resin composition. If the content of C4-LLDPE is greater than the lower limit of the above range, stable moldability can be obtained. If the content of C4-LLDPE is less than the upper limit of the above range, the effect of suppressing the amount of resin used can be fully obtained.
[0036] In the case where the PE resin composition of the present invention includes HDPE, the content of HDPE in the PE resin composition is preferably 5% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 15% by mass or less, relative to the total mass of the PE resin composition. If the content of HDPE is above the lower limit of the above range, the bag making property of the film is stable. If the content of HDPE is below the upper limit of the above range, the effect of suppressing the amount of resin used can be fully obtained.
[0037] Relative to the gross mass of the PE-based resin composition, the content of all resin components in the PE-based resin composition is preferably 20% by mass or more and 50% by mass or less, more preferably 25% by mass or more and 50% by mass or less, and further preferably 30% by mass or more and 50% by mass or less. If the content of all resin components is above the lower limit of the above range, sufficient film strength is easily obtained. If the content of all resin components is below the upper limit of the above range, the effect of suppressing the amount of resin can be fully obtained.
[0038] The inorganic compound contained in the PE resin composition is not particularly limited, and examples thereof include calcium carbonate, titanium oxide, silicon dioxide, clay, talc, kaolin, and aluminum hydroxide. Calcium carbonate is preferred. As the inorganic compound, one kind may be used alone, or two or more kinds may be used in combination.
[0039] As calcium carbonate, it can be so-called heavy calcium carbonate obtained by mechanically crushing limestone, or it can be so-called precipitated calcium carbonate obtained by carbonization method. Calcium carbonate can be calcium carbonate with surface treatment or calcium carbonate without surface treatment. As calcium carbonate, one kind can be used alone, or two or more kinds can be used in combination.
[0040] The average particle size of calcium carbonate is preferably less than 5.0 μm, more preferably less than 3.0 μm. If the average particle size of calcium carbonate is less than the upper limit of the above range, excellent formability can be ensured, and defects such as holes and poor appearance are not easily generated due to agglomeration and the size of the particles themselves during film formation. The lower limit of the average particle size of calcium carbonate is preferably 0.1 μm. The average particle size of calcium carbonate is preferably more than 0.1 μm and less than 5.0 μm. It should be noted that the average particle size of calcium carbonate is measured using an air permeation method.
[0041] The top cut particle size of calcium carbonate is preferably 15 μm or less, and more preferably 10 μm or less. The top cut particle size is measured using an X-ray transmission particle size distribution analyzer.
[0042] The 45 μm sieve residue of calcium carbonate is preferably 0.01 mass % or less. The 45 μm sieve residue is measured using a JIS standard sieve.
[0043] Relative to the gross mass of the resin composition, the content of the inorganic compound in the PE-based resin composition of the present invention is 50% by mass or more and 80% by mass or less, preferably 50% by mass or more and 75% by mass or less, more preferably 50% by mass or more and 70% by mass or less. If the content of the inorganic compound is above the lower limit of the above range, the effect of suppressing the amount of resin can be fully obtained. If the content of the inorganic compound is below the upper limit of the above range, sufficient film strength can be obtained.
[0044] The PE resin composition of the present invention may contain additives as required. Examples of additives include antioxidants, light stabilizers, lubricants, dispersants, pigments, antistatic agents, and animal repellents. The additives may be one or more.
[0045] The content of the additives in the PE-based resin composition of the present invention is preferably 3% by mass or less, more preferably 1% by mass or less, relative to the total mass of the PE-based resin composition.
[0046] The method for producing the PE resin composition of the present invention is not particularly limited, and examples thereof include a method of mixing the components using a single-screw extruder, a multi-screw extruder, a Banbury mixer, a kneader, etc. It is also possible to preliminarily mix the copolymer A and a part of the resin component other than the copolymer A used as needed with an inorganic compound and an additive to prepare a masterbatch, and mix the masterbatch with the rest of the resin component.
[0047] The mixing temperature during production of the PE-based resin composition can be appropriately adjusted, and can be, for example, 150° C. or higher and 190° C. or lower.
[0048] [Polyethylene resin packaging materials]
[0049] The polyethylene resin packaging material of the present invention (hereinafter referred to as "PE resin packaging material") is a packaging material formed from the PE resin composition of the present invention. The PE resin packaging material of the present invention can be formed in a known manner except for using the PE resin composition of the present invention.
[0050] The use of the PE-based resin packaging material is not particularly limited, and examples thereof include garbage bags, shopping bags, fashion bags, storage bags, and packaging bags.
[0051] The method for producing the PE-based resin packaging material of the present invention can adopt a known method other than using the PE-based resin composition of the present invention. For example, a method of forming the PE-based resin composition of the present invention into a film and making a bag by heat sealing can be exemplified. The method of forming into a film can be exemplified by inflation molding, T-die extrusion molding, etc.
[0052] The molding temperature (extrusion temperature) can be adjusted appropriately, and can be set to, for example, 150° C. or higher and 190° C. or lower.
[0053] The thickness of the film may be appropriately set depending on the intended use, and may be, for example, 10 μm or more and 70 μm or less.
[0054] As shown in the above description, in the present invention, the PE resin composition contains the specific copolymer A at a specific ratio. Thus, even if the content of the inorganic compound is large, excellent formability can be ensured, and a film with excellent bagging processability and film strength can be obtained. In addition, the PE resin packaging material obtained using the PE resin composition of the present invention can be manufactured with high productivity and can withstand the packaging and transportation of heavy objects.
[0055] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following descriptions.
[0056] [abbreviation]
[0057] The following abbreviations have the following meanings.
[0058] (Copolymer A)
[0059] A-1: C6-LLDPE, trade name "NOVATEC SF720", manufactured by Japan Polyethylene Co., Ltd., MFR: 0.8 g / 10 min, melting point: 124°C.
[0060] A-2: C6-LLDPE, trade name "HARMOREX NC564A", manufactured by Japan Polyethylene Co., Ltd., MFR: 3.5 g / 10 min, melting point: 124°C.
[0061] A-3: C6-LLDPE, trade name "D139FK", manufactured by Chevron Phillips Chemical Co., MFR: 1.0 g / 10 min, melting point: 90°C.
[0062] A-4: C6-LLDPE, trade name "EVOLUE (registered trademark) 2320", manufactured by Prime Polymers, MFR: 1.8 g / 10 min, melting point: 118°C.
[0063] A-5: C8-LLDPE, trade name "MORETEC (registered trademark) 0168N", manufactured by Prime Polymers, MFR: 1.2 g / 10 min, melting point: 125°C.
[0064] A-6: C8-LLDPE, trade name "0138NK", manufactured by Prime Polymers, MFR: 1.5 g / 10 min, melting point: 117°C.
[0065] (Other polymers B)
[0066] B-1: C4-LLDPE, trade name "FS153S", manufactured by Sumitomo Chemical Asia.
[0067] B-2: C6-LLDPE, trade name "TZ050", manufactured by TOSOH CORPORATION, MFR: 0.5 g / 10 min, melting point: 119°C.
[0068] B-3: C6-LLDPE, trade name "HARMOREX NH645A", manufactured by Japan Polyethylene Co., Ltd., MFR: 8.0 g / 10 min, melting point: 121°C.
[0069] B-4: HDPE, trade name "FJ00952", manufactured by Saudi Basic Industries Corporation.
[0070] [Production Example 1]
[0071] 80% by mass of calcium carbonate (LIGHTON BS-0, average particle size 1.0 μm, manufactured by Beihoku Powder Industry Co., Ltd.) and 20% by mass of copolymer A-5 (C8-LLDPE) particles were mixed in a high-speed mixer for 5 minutes, extruded into strands using a two-axis extruder, and cut into pellets to obtain a masterbatch (MB-1).
[0072] [Production Example 2]
[0073] A masterbatch (MB-2) was obtained in the same manner as in Production Example 1 except that the copolymer A-4 (C6-LLDPE) was used instead of the copolymer A-5.
[0074] [Production Example 3]
[0075] A masterbatch (MB-3) was obtained in the same manner as in Production Example 1 except that the polymer B-1 (C4-LLDPE) was used instead of the copolymer A-5.
[0076] [Example 1]
[0077] As the inflation molding machine, an extruder (manufactured by PLACO) with a barrel inner diameter of 55 mm, a screw L / D of 32, and a die head diameter of The die lip is a 3mm annular die.
[0078] MB-1 is 65% by mass, and polymer B-1 (C4-LLDPE) is 35% by mass. They are metered and fed into an extruder to prepare a PE resin composition, and a tubular film with a thickness of 30 μm and a folded width of 460 mm is formed by inflation molding. The extrusion temperature is set to 170°C, and the inflation ratio is set to about 3.0. Then, a bag body is made by cutting at intervals of 600 mm in the length direction after heat sealing using a bag making machine (manufactured by Nozaki Industries). The heat sealing temperature is 160°C to 180°C.
[0079] The content of calcium carbonate in the film (PE-based resin composition) was 52% by mass, and the content of copolymer A was 13% by mass.
[0080] [Examples 2 to 6]
[0081] A bag was produced in the same manner as in Example 1 except that the composition of the PE-based resin composition was changed as shown in Table 1.
[0082] [Examples 7 to 10]
[0083] A bag was produced in the same manner as in Example 1 except that the composition of the PE-based resin composition was changed as shown in Table 1 and the thickness of the film was changed to 20 μm.
[0084] [Comparative Examples 1 to 5]
[0085] Except that the composition of the PE-based resin composition was changed as shown in Table 2, the same procedure as in Example 1 was carried out to produce a bag.
[0086] [Film formability]
[0087] The stability of the tube during film formation in each example was confirmed, and the formability was evaluated according to the following criteria.
[0088] "1": More stable than ordinary resin (containing no inorganic compound).
[0089] "2": As stable as normal resin.
[0090] "3": Slightly less stable than normal resins, but continuous molding is possible.
[0091] "4": Unstable and unable to form.
[0092] [Bag processing properties]
[0093] The production speed during bag making and the finished shape of the sealed portion were confirmed, and the formability was evaluated according to the following criteria.
[0094] "1": Compared with the case where there is no inorganic substance, the production speed and the finished effect of the sealing part are improved.
[0095] "2": Same as without inorganic matter.
[0096] "3": The finished product of the sealed shape is poor compared to the case without the inorganic substance.
[0097] "4": The production rate is very poor compared to the case without inorganic substances.
[0098] [Film strength]
[0099] The film formed in each example was punctured with a thumb, and the expansion of the rupture when a force was applied to the punctured hole was confirmed, and the film strength was evaluated according to the following criteria.
[0100] (Evaluation Criteria)
[0101] “1”: Not easy to puncture.
[0102] "2": The rupture did not expand from the puncture hole.
[0103] "3": The rupture expands from the puncture hole.
[0104] "4": Fingers are easily punctured.
[0105] Tables 1 and 2 show the composition of the PE-based resin composition, the film thickness, and the evaluation results of each example.
[0106] It should be noted that in Tables 1 and 2, "LLDPE (C6-C8)" refers to LLDPE with 6 to 8 carbon atoms in the α-olefin. "CaCO3 content" refers to the content of calcium carbonate in the PE-based resin composition (film). "LLDPE (C6-C8) content" refers to the total content of LLDPE with 6 to 8 carbon atoms in the α-olefin in the PE-based resin composition (film). "Copolymer A content" refers to the content of copolymer A in the PE-based resin composition (film). "1.0,1.2" in the MFR column refers to the use of LLDPE with an MFR of 1.0 g / 10 minutes and LLDPE with an MFR of 1.2 g / 10 minutes, and the same applies to other columns. "90,118" in the melting point column refers to the use of LLDPE with a melting point of 90°C and LLDPE with a melting point of 118°C, and the same applies to other columns.
[0107] [Table 1]
[0108]
[0109] [Table 2]
[0110]
[0111] As shown in Tables 1 and 2, Examples 1 to 10 in which the PE-based resin composition contained the copolymer A at a specific ratio were excellent in film formability, bag-making processability, and film strength.
[0112] On the other hand, in Comparative Examples 1-4 in which the PE resin composition did not contain copolymer A and Comparative Example 5 in which the content of copolymer A in the PE resin composition was small, at least one of film formability, bag forming processability and film strength was poor.
Claims
1. A polyethylene resin composition, comprising an inorganic compound, an ethylene-α-olefin copolymer and a high-density polyethylene, wherein: The ethylene-α-olefin copolymer comprises: an ethylene-α-olefin copolymer A having 6 to 8 carbon atoms in the α-olefin and a melt flow index of 1.0 g / 10 minutes or more and 2.0 g / 10 minutes or less; and a linear low-density polyethylene having 4 carbon atoms in the α-olefin, The melt flow index is a value obtained by applying a load of 2.16 kg to a resin heated to 190° C. and measuring the amount of resin flowing out of an orifice with a diameter of 2.09 mm for 10 minutes. The ethylene-α-olefin copolymer A comprises a linear low-density polyethylene having 6 carbon atoms in the α-olefin and a linear low-density polyethylene having 8 carbon atoms in the α-olefin. The content of the inorganic compound is 50% by mass or more and 80% by mass or less relative to the total mass of the resin composition, The content of the ethylene-α-olefin copolymer A is 10% by mass or more and 25% by mass or less relative to the total mass of the resin composition. The content of the linear low-density polyethylene having 4 carbon atoms which is an α-olefin is 10% by mass or more and 20% by mass or less based on the total mass of the resin composition, The content of the high-density polyethylene is 5 mass % or more and 15 mass % or less relative to the total mass of the resin composition.
2. The polyethylene resin composition according to claim 1, wherein The melting point of the ethylene-α-olefin copolymer A is 90° C. or higher and 130° C. or lower.
3. The polyethylene resin composition according to claim 1 or 2, wherein The inorganic compound is calcium carbonate. 4 . A polyethylene resin packaging material, comprising the polyethylene resin composition according to claim 1 .
5. The polyethylene resin packaging material according to claim 4, which is a garbage bag, a shopping bag, a fashion bag, a storage bag or a packaging bag.
Citation Information
Patent Citations
Resin composition for garbage bag, garbage bag, and method for producing garbage bag
JP2018021121A
Polyethylene resin composition and its film, porous film and molded articles and method of manufacturing the porous film
JP2002003661A